Glycans as a key factor in self and nonself discrimination: impact on the breach of immune tolerance. Issue 12 (13th April 2022) - Alves, Inês; Fernandes, Ângela; Santos‐Pereira, Beatriz; Azevedo, Catarina M.; Pinho, Salomé S.
Abstract : Glycans are carbohydrates that are made by all organisms and covalently conjugated to other biomolecules. Glycans cover the surface of both human cells and pathogens and are fundamental to defining the identity of a cell or an organism, thereby contributing to discriminating self from nonself. As such, glycans are a class of 'Self‐Associated Molecular Patterns' that can fine‐tune host inflammatory processes. In fact, glycans can be sensed and recognized by a variety of glycan‐binding proteins (GBP) expressed by immune cells, such as galectins, siglecs, and C‐type lectins, which recognize changes in the cellular glycosylation, instructing both pro‐inflammatory and anti‐inflammatory responses. In this review, we introduce glycans as cell‐identification structures, discussing how glycans modulate host–pathogen interactions and how they can fine‐tune inflammatory processes associated with infection, inflammation and autoimmunity. Finally, from the clinical standpoint, we discuss how glycoscience research can benefit life sciences and clinical medicine by providing a source of valuable biomarkers and therapeutic targets for immunity. Abstract : Glycans have an enormous power to discriminate self/nonself as they constitute a fundamental molecular ID of both human cells and pathogens. We discuss the concept of glycan mimicry associated with the breach of immune tolerance and the potential application of glycans as promising diagnostic/prognostic biomarkers or as novel immunomodulatory therapies against infections and autoimmune diseases.